Shell buckling: from morphogenesis of soft matter to prospective applications. (20th July 2018) - Lin, Sen; Xie, Yi Min; Li, Qing; Huang, Xiaodong; Zhang, Zhe; Ma, Guowei; Zhou, Shiwei
Abstract: Being one of the commonest deformation modes for soft matter, shell buckling is the primary reason for the growth and nastic movement of many plants, as well as the formation of complex natural morphology. On-demand regulation of buckling-induced deformation associated with wrinkling, ruffling, folding, creasing and delaminating has profound implications for diverse scopes, which can be seen in its broad applications in microfabrication, 4D printing, actuator and drug delivery. This paper reviews the recent remarkable developments in the shell buckling of soft matter to explain the most representative natural morphogenesis from the perspectives of theoretical analysis in continuum mechanics, finite element analysis, and experimental validations. Imitation of buckling-induced shape transformation and its applications are also discussed for the innovations of sophisticated materials and devices in future.